A focus on Sjogren’s Dry Eye Disease - pathogenesis, patient management, and new advancements in therapy - Uram, Ewa; Bogacz, Rafał; Gaik, Magdalena; Magda, Inga; Woźniak , Justyna; Womperski, Karol; Osuch, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: Sjogren’s syndrome (SS) is a systemic chronic inflammatory autoimmune disease of unknown etiology that primarily affects exocrine glands. Most commonly Sjogren’s syndrome presents with dryness of the mouth and eyes, but it can also affect major organs and systems of the body and increase the risk of non-Hodgkin lymphoma. Due to non-specific symptoms that pose diagnostic challenges and a lack of standardized screening tools and classification criteria, the global incidence and prevalence of the disease are hard to evaluate. Studies estimate that Sjogren’s syndrome affects between 400,000 to 3.1 million adults worldwide and most likely is a condition significantly underdiagnosed. Aim of the study: Review of current knowledge about Sjogren’s dry eye disease, underlying pathologies, diagnostic problems, and current treatment options with a focus on the most recent advancements in therapy. Methods and materials: A review of chosen literature in the PubMed database, MDPI database, and GoogleScholar in the years 2000-2023 was conducted using the following keywords: “Sjogren’s syndrome”, “Sjogren’s syndrome ophthalmology”, “Sjogren’s dry eye syndrome”, “Sjogren’s syndrome associated dry eye”, “Lymphoma in Sjogren’s syndrome”, “Diagnosing Sjogren’s syndrome dry eye”, “Sjogren’s syndrome epidemiology”. Results: Sjogren’s syndrome is a far from rare autoimmune disease that affects many organs of the body and can significantly lower quality of life and increase mortality and morbidity. Due to its surreptitious symptom onset, Sjogren’s syndrome is commonly underdiagnosed. New diagnostic and treatment modalities for Sjogren’s syndrome dry eye are on the horizon. Conclusions: Standardized, internationally recognized criteria and a high level of clinical suspiciousness are needed for a timely and accurate diagnosis of Sjogren’s syndrome. Quick diagnosis is a significant facilitating factor for maintaining a high quality of life in Sjogren’s syndrome dry eye.